Whole genome sequencing of Entamoeba nuttalli reveals mammalian host-related molecular signatures and a novel octapeptide-repeat surface protein. - Masayuki Tanaka; Takashi Makiuchi; Tomoyoshi Komiyama; Takashi Shiina; Ken Osaki; Hiroshi Tachibana (PLoS Neglected Tropical Diseases)
The enteric protozoa Entamoeba histolytica is the causative agent of amebiasis, which is one of the most common parasitic diseases in developed and developing countries. Entamoeba nuttalli is the genetically closest species to E. histolytica in current phylogenetic analyses of Entamoeba species, and is prevalent in wild macaques. Therefore, E. nuttalli may be a key organism in which to investigate molecules required for infection of human or non-human primates. To explore the molecular signatures of host-parasite interactions, we conducted de novo assembly of the E. nuttalli genome, utilizing self-correction of PacBio long reads and polishing corrected reads using Illumina short reads, followed by comparative genomic analysis with two other mammalian and a reptilian Entamoeba species. The final draft assembly of E. nuttalli included 395 contigs with a total length of approximately 23 Mb, and 9,647 predicted genes, of which 6,940 were conserved with E. histolytica. In addition, we found an E. histolytica-specific repeat known as ERE2 in the E. nuttalli genome. GO-term enrichment analysis of mammalian host-related molecules indicated diversification of transmembrane proteins, including AIG1 family and BspA-like proteins that may be involved in the host-parasite interaction. Furthermore, we identified an E. nuttalli-specific protein that contained 42 repeats of an octapeptide ([G,E]KPTDTPS). This protein was shown to be localized on the cell surface using immunofluorescence. Since many repeat-containing proteins in parasites play important roles in interactions with host cells, this unique octapeptide repeat-containing protein may be involved in colonization of E. nuttalli in the intestine of macaques. Overall, our draft assembly provides a valuable resource for studying Entamoeba evolution and host-parasite selection.